The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.cardfail.2020.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Case Reports of Implantable Cardiac Device Physiologic Sensor Changes in Subjects with Coronavirus Disease-2019 Infection

Abstract: The severe acute respiratory syndrome novel coronavirus-2 pandemic has established a new set of challenges to health care delivery. Remotely monitored physiologic sensors on implantable cardiac devices can provide insight into the differential diagnosis of dyspnea in the heart failure population. We report on a unique pattern of sensor deviations that seem to occur specifically with severe acute respiratory syndrome novel coronavirus-2 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“… 18 Numerous individual case studies with HeartLogic capable devices and SARS‐CoV‐2 infections have also suggested that individual sensors may help identify patients who are COVID‐19 positive, even before patients themselves report symptoms. 19 , 20 , 21 , 22 The sensor changes reported in these individual cases are consistent with the quantitative trends that we report here, including increasing respiratory rate and impedance.…”
Section: Discussionsupporting
confidence: 89%
“… 18 Numerous individual case studies with HeartLogic capable devices and SARS‐CoV‐2 infections have also suggested that individual sensors may help identify patients who are COVID‐19 positive, even before patients themselves report symptoms. 19 , 20 , 21 , 22 The sensor changes reported in these individual cases are consistent with the quantitative trends that we report here, including increasing respiratory rate and impedance.…”
Section: Discussionsupporting
confidence: 89%
“…118 However, the utility of this technology in differentiating HF from COVID-19related lung injury yielded mixed results. 119,120 The post-pandemic world of remote monitoring and telemedicine for patients with HF is likely to include all forms of care including virtual, in-person, and remote assessments. Wearables will may see accelerated adoption, 121 as smartwatch heart rate and rhythm monitoring may effectively trigger the need to seek medical attention.…”
Section: Challenges and Innovations In Hf Care Delivery During The Pandemicmentioning
confidence: 99%
“…The use of remote monitoring and telemedicine was forever changed by the COVID‐19 pandemic and are now more firmly entrenched in healthcare delivery than ever before. Multiple publications have also shown how the HeartLogic sensors are directly impacted in patients that contracted COVID‐19 39–44 . As of 6 October 2020, six subjects from PREEMPT were reported to have presented to the hospital with COVID‐19 and were included in an analysis comparing sensor changes with COVID‐19 to those presenting with decompensated HF or pneumonia 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple publications have also shown how the HeartLogic sensors are directly impacted in patients that contracted COVID‐19. 39 , 40 , 41 , 42 , 43 , 44 As of 6 October 2020, six subjects from PREEMPT were reported to have presented to the hospital with COVID‐19 and were included in an analysis comparing sensor changes with COVID‐19 to those presenting with decompensated HF or pneumonia. 45 COVID‐19 was distinguishable from worsening HF by an extreme and fast rise in respiratory rate and no changes in S3.…”
Section: Discussionmentioning
confidence: 99%